Discovery and characterization of a novel peptide inhibitor against influenza neuraminidase. Issue 1 (22nd January 2020) - Chen, Jianmei; Feng, Shujun; Xu, Yurui; Huang, Xinyu; Zhang, Jikang; Chen, Jiao; An, Xueying; Zhang, Yu; Ning, Xinghai
Abstract : An optimized octapeptide (errKPAQP), exhibits nanomolar affinity to influenza neuraminidase, can notably inhibit neuraminidase activity, and protect mice from influenza infection in vivo, indicating that errKPAQP is a promising anti-influenza drug. Abstract : Neuraminidase, an abundant glycoprotein on the influenza virus surface, plays crucial roles in virus replication. Targeting neuraminidase could be a splendid way for the prevention of the spread of influenza infections. Herein, we have identified an octapeptide (errKPAQP) from a synthesized peptide library, originating from mimicking the binding pocket of oseltamivir in neuraminidase, as a potent peptide neuraminidase inhibitor. The docking-based virtual studies showed that errKPAQP exhibited a strong binding affinity (a docking score of −20.03) and nanomolar affinity (11 nM) to influenza neuraminidase, and can inhibit neuraminidase activity at a concentration as low as 4.25 μM, leading to effective protection of MDCK cells from influenza virus-induced death and replication. Furthermore, errKPAQP presented low hemolytic activity, minimal cytotoxicity, and good pharmacokinetic characteristics, which are imperative for an anti-influenza drug. Importantly, errKPAQP was capable of reducing influenza virus-induced inflammation, the serious damage to the lung tissues, and mortality rates in infected mice, indicating that it could protect against the lethal challenge of influenza viruses in vivo . Therefore, we have developed a novel neuraminidase peptide inhibitor with advantageous biological properties and high inhibitory activity towards neuraminidase, and it can serve as a promising anti-influenza drug.